Improved Dye Survival in Expansion Microscopy through Stabilizer‐Conjugated Linkers. Issue 66 (29th September 2022) - Wen, Gang; Leen, Volker; Jia, Yuqing; Rohand, Taoufik; Hofkens, Johan
Abstract: Expansion microscopy (ExM) has been widely used to detect biomolecules in cultured cells and tissue samples due to its enablement of super resolution imaging with conventional microscopes, via physical expansion of samples. However, reaction conditions inherent to the process bring about strong fluorescent signal loss during polymerization and digestion and thus limit the brightness of the signal obtained post expansion. Here, we explore the impact of stabilizer‐containing organic fluorophores in ExM, as a mitigation strategy for this radical‐induced dye degradation. Through direct conjugation of 4‐nitrophenylalanine (NPA) to our previously developed trifunctional reagents, we validate and demonstrate that these multifunctional linkers enable visualization of different organelles with improved fluorescent intensity, owning to protection of the dyes to radical induced degradation as well as to photoprotection upon imaging. At this point, we cannot disentangle the relative contribution of both mechanisms. Furthermore, we report anchoring linkers that allow straightforward application of NPA or Trolox to commercially available fluorophore‐conjugated antibodies. We show that these anchoring linkers enable complete retention of biological targets while increasing fluorophore photostability. Our results provide guidance in exploring these stabilizer‐modified agents in ExM and methods for increased signal survival through the polymerization steps of the ExM protocols. Abstract : A series of stabilizer‐containing multifunctional molecules has been developed and evaluated in expansion microscopy. These multifunctional molecules not only enable effective protection of dyes from radicals during polymerization, but also improve photostability while showing no negative impact on polymerization.